DC AC motors switching controller - Ahmad Zhafir, Ahmad Wahid (2009)
This project is about controlling the switching of DC and AC motors. The DC motor has large starting torque compare to AC motors and therefore they always used as starting motor to move the electric vehicle. On the other hand the AC motors is consider maintenance free and suitable for electric vehicle as well. It is common practise to put these motor in an electric vehicle. This project applied how to operate electric train. The speed of the train is varied by moving the voltage control on the transformer panel. The higher the voltage, the greater the speed. Some transformers provide at least two different voltage ranges. The lower range is used for light trains the higher range for heavier trains. The problem is how to switch ON and OFF both motors when is required. This project will switch ON DC motor first and after certain speed which is will set by user and without considering the load AC motor is ON automatically. If the speed is lower than set value the DC motor will still ON. Both motors are running simultaneously once the temperature reached at certain value (set by user). The motors back to normal sequence of operation temperature of both motor back to normal. The controller also controls the forward and reverse direction of the motors.